Efficacy of therapies for intermediate-stage hepatocellular carcinoma: systematic review and network meta-analysis - Zong, Shaoqi; Yang, Yifan; Yin, Zifei; Feng, Lanyun; Wang, Kun; Chen, Hao; Chen, Zhen; Meng, Zhiqiang; Hua, Yongqiang (Frontiers in Immunology, 2025)
BackgroundTransarterial chemoembolization (TACE) is recommended for intermediate-stage hepatocellular carcinoma (HCC). However, several therapies have shown better efficacy than TACE, meaning that the optimal therapy is unclear. We addressed this uncertainty using network meta-analysis (NMA).MethodsA literature review was performed up to March 15, 2024. Efficacy was evaluated using overall survival (OS) and progression-free survival (PFS). The hazard ratios (HRs) and 95% confidence intervals (CIs) were extracted from the Kaplan–Meier curves. A random-effects NMA was conducted, and subgroup analysis was performed according to the tumor number, tumor size, viral etiology, and alpha fetoprotein (AFP) level. The efficacy of the different therapies was ranked based on the P-score.ResultsA total of 38 studies, 10,972 patients, and 13 therapeutic regimens were eligible. Seven therapies showed OS benefit over TACE, including TACE plus microwave ablation (MWA) (HR = 0.24, 95%CI = 0.06–0.91), TACE plus liver resection (HR = 0.35, 95%CI = 0.22–0.57), liver resection plus RFA (HR =0.49,95%CI=0.35-0.70), TACE plus immune checkpoint inhibitors (ICIs) plus tyrosine kinase inhibitors (TKIs) (HR = 0.51, 95%CI = 0.27–0.95), liver resection (HR = 0.54, 95%CI = 0.45–0.65), and TACE plus radiofrequency ablation (RFA) (HR = 0.57, 95%CI = 0.36–0.93). However, no therapies improved the PFS better than TACE alone. Subgroup analysis indicated that liver resection plus TACE showed the best OS for patients with hepatitis B virus (HBV) infection.ConclusionsSeven therapies showed better efficacy than TACE alone for particular patients with intermediate-stage HCC.Systematic review registrationhttps://www.crd.york.ac.uk/, PROSPERO CRD42023459740.